The Cilappatikaram : The tale of an anklet - Atikal, LLankó
Men and women of Maturai of the four temples I curse this city. Its king erred in killing the man I loved One of the world's masterpieces, The Cilappatikaram (5th century ce) by Ilanko Atikal is India's finest epic in a language other than Sanskrit. It spells out in unforgettable verse the problems that humanity has been wrestling with for a long time: love, war, evil, fate and death. The Tale of an Anklet is the love story of Kovalan and Kannaki. Originating in Tamil mythology, the compelling tale of Kannaki her love, her feats and triumphs, and her ultimate transformation to goddess follows the conventions of Tamil poetry and is told in three phases: the erotic, the heroic and the mythic. This epic ranks with the Ramayana and the Mahabharata as one of the great classics of Indian literature and is presented for the first time in a landmark English verse translation by the eminent poet R. Parthasarathy, making it accessible to a wider audience. Winner of the 1995 Sahitya Academy prize for Translation (English), the 1994 PEN/ Book-of-the-Month Club Translation Citation of the PEN American center, and the 1996 Association for Asian Studies A.K. Ramanujan Book Prize for Translation.